Measurement of blade detection of an unmanned intermeshng rotor helicopter - Voigt, A.E.; Dauer, J.C.; Knaak, F. (My University, 2017)
The dynamic behavior of intermeshing rotor blades is complex and subjected to rotor-rotor-interactions like oblique blade-vortex and blade-wake interactions. To gain a better understanding of these effects a blade deflection measurement method is proposed in this paper. The method is based on a single camera per rotor blade depicting the rotor blade from a position fixed to the rotor head. Due to the mounting position of the camera close to the rotational plane the method is called In-Plane Blade Deflection Measurement (IBDM). The basic principles, data processing and measurement accuracy are presented in the paper. The major advantages of the proposed method are the applicability to both, flight and wind tunnel trials, as well as the usability for multi-rotor configurations having a significant rotor overlap. Furthermore comparisons to other blade deflection measurement methods are presented. Finally, experimental data of a flight test of an unmanned intermeshing helicopter is presented.